The toll of traffic-related fatalities in a metropolitan Italian area through the experience of the Department of Legal Medicine. Issue 2 (2nd April 2016) - Amadasi, Alberto; Cerutti, Elisa; Spagnoli, Laura; Blandino, Alberto; Rancati, Alessandra; Gallo, Carlotta; Mancini, Elisabetta; Rizzi, Vittorio; Cattaneo, Cristina
Abstract : Despite the introduction of new traffic laws in Italy, traffic-related deaths are still a huge burden. The study presents data and medico-legal issues behind traffic deaths in Milan between 2001 and 2012 (1506 traffic-related deaths). Data were collected from the database of the Department of Legal Medicine: 79.4% males and 20.6% females (mean age 44.14). The target group concerned traumatic deaths as a consequence of the accident as well as deaths not directly related to an accident. Although 6.1% were non-traumatic deaths (cause of death unconnected to the accident, i.e. because of a heart attack, or when death occurred after survival and cause of death was not related certainly to the accident), multiple skeletal/visceral injuries were the main cause of death (57.9%), occurring in motorcyclists the most (63.7%). Injuries to the skull and brain were the second cause of death (25.9%). Victims were mostly males (79.4%) and drivers (77.6%). Fifty-five per cent were deaths on-scene, while 45% survived. Other variables were also considered: medications, medical history, and drugs/alcohol/smoke. A downward trend in traffic-related fatalities was evident, but the toll is still high. This study should be a glimpse at the actual situation, since it is indicative of a metropolitan area where autopsies are systematically performed.